THE RELATIONSHIP OF PREGNANT WOMEN'S CHARACTERISTICS TO KNOWLEDGE ABOUT HIGH-RISK PREGNANCY - Rusmita, Eli; Reginita, Silvya (Journal of Maternity Care and Reproductive Health, 2023)
Hight risk pregnancy is a condition that can affect the health of the mother and baby in the womb and this research aims to identify the relationship between characteristics of pregnant women and knowledge of high risk pregnancy. The research method was analytical observational with a cross sectional approach with 86 pregnant women respondents in Neglasari village, Majalaya district, bandung regency in May 2023. Data was collected using a questionnaire which was then analyzed using shi square. The results of the study showed that the highest frequency of lack of knowledge at age ≥ 35 years was 28 respondets (32,56%), the highest frequency of lack of knowledge with junior high school education was 24 respondents (27,9%), and the highest frequency of lack of knowledge with no work was as many as 39 respondents (27,9%) and the highest frequency of poor knowledge primiparous parity was 17 respondents (19,77%). The conclusion of the research is that there is a relationship between the characteristics of pregnant women and knowledge of high-risk pregnancies, so it is recommended to the Neglasari village head to increase socialization and helth education related to improving maternal health during pregnancy so that high-risk pregnancies can be prevented.